Two new algorithms for discrete boundary value problems. (1990) - Agarwal, Ravi P.; Nanda, Tara R.
Abstract : We propose two new methods of constructing the solutions of linear multi-point discrete boundary value problems. These methods are applied to solve some continuous two-point boundary value problems which are known to be numerically unstable.